THE INFLUENCE OF DIGITAL LEADERSHIP, DIGITAL CAPABILITIES, AND ORGANIZATIONAL CULTURE ON SUSTAINABLE DIGITAL TRANSFORMATION AT THE YOGYAKARTA PALACE - Ani Juwita Handayani; Edi Sugiono; Irma Setyawati; Rahayu Lestari (PT. Jurnal Center Indonesia Publisher, 2026)
For businesses in all industries, especially historic institutions that need to strike a balance between modernity and cultural preservation, digital transformation has emerged as a strategic necessity. With an emphasis on the Yogyakarta Palace environment, this study uses a Systematic Literature Review (SLR) methodology in accordance with PRISMA principles to examine the impact of organizational culture, digital leadership, and digital capabilities on digital transformation. From the Scopus, Web of Science, and Google Scholar databases, 68 articles with peer review published between 2022 and 2026 were methodically found, vetted, and examined. The results show that organizational culture acts as a fundamental enabler that dictates the sustainability of transformation initiatives, digital leadership acts as a strategic catalyst for starting transformation, and digital capabilities offer the necessary organizational competencies for carrying out digital strategies. According to the integrative study, these three factors work together rather than separately, indicating that their simultaneous development is necessary for a digital transformation to be successful. This review presents practical implications for human resource management practitioners as well as a thorough theoretical framework for comprehending digital change inside legacy institutional settings.